Formulation and evaluation of Acyclovir compressed lozenges - Dalya Badry Khudhair; Wedad K. Ali (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2022)
Lozenges are formulations of solid dosage form which tend to liquefy in mouth or pharynx. They could be consisting of one or more drugs in a flavored and sweetened base. They are recommended to treat local mouth or pharynx irritation or infection, or they may be used also for systemic combi-